A clinical study of liposuction followed by lymphovenous anastomosis for treatment of breast cancer-related lymphedema - Chang, Kun; Xia, Song; Liang, Chen; Sun, Yuguang; Xin, Jianfeng; Shen, Wenbin (Frontiers in Surgery, 2023)
Objective In this work, we studied the clinical effect of liposuction followed by lymphovenous anastomosis (LVAs) for the treatment of breast cancer-related lymphedema (BCRL). Methods We analyzed 158 patients with unilateral upper limb BCRL who underwent liposuction followed by LVAs 2–4 months later. Arm circumferences before and 7 days after the combined treatments were prospectively recorded. Circumferences of different upper extremities were measured before the procedure, 7 days after LVAs, and during the follow-ups. Volumes were calculated with the frustum method. During the follow-ups, the conditions of patients’ treated arms, i.e., the frequency of erysipelas episodes and dependence on compression garments, were recorded. Results The mean circumference difference between two upper limbs decreased significantly from M (P25, P75) of 5.3 (4.1, 6.9) preoperatively to 0.5 (−0.8, 1.0) (P < 0.05) 7 days after treatments, while at follow-up 0.3 (−0.4, 1.0). The mean volume difference decreased significantly from M (P25, P75) of 838.3 (662.4, 1,129.0) preoperatively to 7.8 (−120.3, 151.4) (P < 0.05) 7 days after treatments, while at follow-up 43.7 (−59.4, 161.1). The incidence of erysipelas also significantly decreased (P < 0.05). 6.3% of patients were already independent of compression garments during the past six months or even more. Conclusion Liposuction followed by LVAs is an effective method for the treatment of BCRL.